Los "Vocablos para traducir a Salustiano" de José de Acosta - Antón Martínez, Beatriz; Martínez Ortega, Ricardo (1993)
A good sign of José de Acosta's (1767-1822) interest in Latin, pedagogy and Humanities is shown in his work Asuntos de Latinidad, where we can find different glossaries useful in the translation of latin authors. This paper deals with the terms that Acosta supplies so that Sallust can be translated. We have discovered to our pleasant surprise, that Acosta did not consider it sufficient to look up ah the available scholastic dictionaries in bis time, but his teaching concerns and his scientific curiosity went firther than any of bis contemporaq colleagues, because he used in bis research R. Estienne Thesaurus Linguae Latinae, lexicon whose high quality is beyond all doubt.
Keywords: Acosta, José de